Mediating role of self-compassion, emotional regulation on the relationship between, and Psychological Distress (Journal of Basic and Applied Research in Biomedicine, 2022)
Objective: University students experience higher levels of psychological distress compared to the general population. Clark and Watson (1991) introduced the Tripartite Model, proposing that psychological distress is operationalised by depression, anxiety and stress. Although self-compassion and emotional regulation have been shown to be associated with lower levels of psychological distress, the relationship between these variable has been vastly understudied. Method: The study employed a cross-sectional design using online questionnaires measuring emotional regulation, self-compassion and psychological distress (depression, anxiety and stress). Data were collected from 89 Australian university students. Results: As predicted, bivariate correlations found that self-compassion, emotional regulation, and psychological distress (depression, anxiety and stress), were all significantly correlated. Regression analyses highlighted that self-compassion significantly accounted for 44% of the variance of psychological distress; emotional regulation did not significantly account for variance of psychological distress. Following this, three single mediations based on significant correlations were conducted. Mediation analyses found that emotional regulation mediated the relationship between self-compassion and depression. However emotional regulation did not mediate the relationship between self-compassion and anxiety, or self-compassion and stress. Conclusions: The results highlight the mediating role of emotional regulation on self-compassion and depression. Future research is warranted to better understand the role of emotional regulation the depression–intrusion relationship, which may shed light on the clinical applicability of self-compassion targeted intervention for enhancing emotional regulation in university students experiencing depression.